2016
DOI: 10.1542/peds.2015-2232
|View full text |Cite
|
Sign up to set email alerts
|

Turner Syndrome and Celiac Disease: A Case-Control Study

Abstract: OBJECTIVE: Turner syndrome (TS) is the most common sex chromosome abnormality in females. Previous research has indicated a high prevalence of celiac disease (CD) in TS, but data have mostly been limited to case series at tertiary centers. We aimed to examine the risk for CD in individuals with TS compared with the general population.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0
7

Year Published

2017
2017
2021
2021

Publication Types

Select...
4
2
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 45 publications
(34 citation statements)
references
References 47 publications
0
27
0
7
Order By: Relevance
“…Celiac disease is the second most common autoimmune disease described in women with Turner syndrome, present in approximately 8% (Gravholt, Andersen, et al, , table 2). There is a twofold increased risk of celiac disease in girls with Turner syndrome younger than 5 years of age (Marild, Stordal, Hagman, & Ludvigsson, ) which increases to a more than fivefold increase after the age of 10 years. The relative risk in adults, when compared to the general population, is increased by as much as 42‐fold (Bakalov et al, ).…”
Section: Autoimmune Disordersmentioning
confidence: 99%
“…Celiac disease is the second most common autoimmune disease described in women with Turner syndrome, present in approximately 8% (Gravholt, Andersen, et al, , table 2). There is a twofold increased risk of celiac disease in girls with Turner syndrome younger than 5 years of age (Marild, Stordal, Hagman, & Ludvigsson, ) which increases to a more than fivefold increase after the age of 10 years. The relative risk in adults, when compared to the general population, is increased by as much as 42‐fold (Bakalov et al, ).…”
Section: Autoimmune Disordersmentioning
confidence: 99%
“…The copyright holder for this preprint this version posted April 14, 2020. . https://doi.org/10.1101/2020.04.09.20060012 doi: medRxiv preprint dysfunction is a common feature of Turner syndrome along with autoimmune celiac disease 33,34 , while aortic valve disease may also accompany component autoimmune phenotypes of Multiple Sclerosis 35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…19 Several studies have demonstrated that CD is more commonly observed in patients with TS than those in the general population. [20][21][22][23][24] Therefore, it has been recommended that patients with TS be monitored for CD. 11 There is a lack of systematic reviews on the strength of association between specific genetic disorders and CD.…”
Section: Introductionmentioning
confidence: 99%